KEANEKARAGAMAN JENIS VEGETASI PAKAN BADAK FASE SEMAI DI ZONA KHUSUS KONSERVASI TAMAN NASIONAL WAY KAMBAS - Riyan Maulana; Indriyanto -; Afif Bintoro (Lambung Mangkurat University-Indonesia, 2021)
The Sumatran rhinos (Dicerorhinus sumatrensis) is the smallest of the five species of rhinoceros that still alive. Way Kambas National Park (TNWK) is captivity semi-insitu of Dicerorhinus sumatrensis. The Sumatran rhinos are herbivorous with a preference of young tree (seedling), leaves, fruits, and shoots.The importance of knowledge about study of feed sumatran rhinos for conservationof rhino in TNWK. The purpose of the study is to identifies rhino feed on seedling growth level in the conservation zones TNWK. The research used line transect method. The first line and plot determined randomly then the next line and plots was sistematically. The observation plots had measurement with amount 2m x 2m of seedling growth level in big plot with amount 20m x 20m with spacing between plot in line 500 m with total 98 plots. The results of this study concluded that there were 28 types of seedling rhino feed which was found to be the most abundant and evenly distributed based on the important value index, are Ixora sp. is 16.73 and then Antidesma neurocarpum Miq is 14.4 and Dillenia excelsa is 10.89. Biodiversity index is 3.57 and evennes index is 0.84.